The Agave genus in the genomics era: evolution, biodiversity, and sustainable innovation - Dolores Javier Sánchez González (Academia Molecular Biology and Genomics)
Agave species represent an exceptional model of genetic diversity, climate resilience, and bioeconomic potential. The common ancestor of all mezcals, called “vino mezcal”, emerged in Colima and Jalisco in the 16th century, and from it came famous mezcals such as raicilla, tequila, bacanora, tuxca, and mezcal. Characterized by a unique bimodal karyotype and large nuclear genomes, Agave exhibits complex patterns of polyploidization, chromosomal rearrangements, and repetitive DNA accumulation that underpin its adaptation to arid environments. Advances in genomic research have revealed critical insights into its structure, emphasizing the urgent need for genetic conservation amid pressures from clonal propagation and industrial monoculture. The integration of high-throughput sequencing, cytogenetic mapping, and comparative genomics has opened new avenues for sustainable agriculture and biotechnological innovation, including biofuel production, bioplastics, and pharmaceutical applications. Nevertheless, maintaining biodiversity through the conservation of wild populations and the promotion of traditional agricultural practices remains critical for safeguarding the genus’s evolutionary potential. This review consolidates the latest findings in chromosome biology, genome architecture, and biotechnological applications of Agave, positioning it as a key species for green innovation in the face of global climate change. By bridging ecological heritage with modern genomic tools, Agave emerges not only as a crucial resource for economic development but also as a model of sustainable adaptation strategies for future agricultural systems.